Gamifikasi untuk Meningkatkan Partisipasi Masyarakat Dalam Mendukung Konsep Ketahanan Terhadap Bencana - Asep Id Hadiana; Rezki Yuniarti; Agus Komarudin (LPPM STMIK IKMI Cirebon, 2022)
This study discusses the use of gamification techniques in enhancing community involvement in disaster emergency planning activities. The objective of this study is to explore how gamification can be incorporated into disaster emergency planning programs to enhance disaster resilience in West Bandung Regency. The study was conducted by collecting data from respondents through online questionnaires and structured interviews to evaluate the effectiveness of gamification techniques in motivating community participation in disaster emergency planning. The results show that the use of gamification techniques can increase community participation in disaster emergency planning programs and can also influence the democratic process. Therefore, this study provides evidence that the use of gamification techniques can be an effective tool in enhancing the efficiency and intelligence of disaster emergency planning and can help achieve the goal of disaster resilience in West Bandung Regency.